Confederation as a form of government and its features: of a theoretical and historical analysis. (Journal of actual problems of jurisprudence, 2016)
This paper examines the theoretical and practical problems of the Confederation as a special form of government; historical and legal conditions and causes of the Confederation; problems of development of the legal basis for interaction of confederation; provides an analysis of categorical conceptual apparatus. In this paper we study historical examples of confederations in Kazakhstan; author conducted analysisof the legal foundations for the development of modern confederations; identified the advantages and disadvantages of this form of government. According to the author, the confederation as a union of independent states is the future development of the former Soviet Union. All this determines the scientific novelty of the study.
Keywords: confederation; the state; power; shape; territory; commonwealth